A case and literature review of orbital microcystic adnexal carcinoma. (2nd November 2018) - Brent, Alexander J.; Deol, Sundeep S.; Vaidhyanath, Ram; Saldanha, Gerald; Sampath, Raghavan
ABSTRACT: Microcystic adnexal carcinoma (MAC) is a very rare and locally aggressive sweat gland tumour. MAC has been well reported presenting as a periocular cutaneous lesion, rarely with subsequent direct orbital invasion and only once as a primary orbital lesion. Local recurrence is frequent after primary surgical excision and the role of adjuvant radiotherapy is ill-defined. We describe a case of orbital MAC treated successfully with radiotherapy after incomplete margin clearance post exenteration surgery and review the associated literature.